Edukasi Kesehatan tentang Gizi Seimbang pada Balita dan Pemeriksaan Antropometri - Fatmawati, Tina Yuli; Kusuma, Ratu; Putri, Vevi Suryenti (Universitas Baiturrahim, 2024)
One effort to stay healthy and fit and avoid disease is by maintaining balanced nutrition. The role of parents in this case is very important in fulfilling children's nutrition for optimal growth and development. To get good nutrition, parents need good nutritional knowledge so they can provide a balanced menu of choices. The aim of this community service is to increase mothers' knowledge about balanced nutrition and the nutritional status of toddlers by checking the height (TB) and weight (BB) of toddlers. The service methods applied are lectures, discussions, anthropometric examinations (BB and TB), pretest and posttest. The Education was carried out for mothers with toddlers who visited the KIA polyclinic at the Koni Health Center, Jambi City. The result of this community service was an increase in mother's knowledge from 30% to 100%. It can be concluded that after education, mothers can understand how to arrange a balanced menu for toddlers and are able to measure the BB and TB of toddlers